Cell proliferation activity in posterior uveal melanoma after Ru-106 brachytherapy: an EORTC ocular oncology group study. Issue 10 (1st October 2001) - Pe'er, Jacob; Stefani, Fritz H; Seregard, Stefan; Kivela, Tero; Lommatzsch, Peter; Prause, Jan U; Sobottka, Beate; Damato, Bertil; Chowers, Itay
Abstract : AIM: To evaluate the cell proliferation activity in posterior uveal melanomas after Ru-106 brachytherapy. METHODS: Eyes containing choroidal or ciliary body melanoma from seven ocular oncology centres, which were enucleated after first being treated by Ru-106 brachytherapy and which had enough melanoma tissue to enable histological assessment, were included. The 57 eligible specimens were divided into a group of 44 eyes that were enucleated because of tumour regrowth, and a non-recurrent group of 13 eyes that were enucleated because of complications such as neovascular glaucoma. 46 non-irradiated eyes harbouring uveal melanoma served as a control group. All specimens underwent routine processing. They were cut into 5 μm sections, and were stained with two main cell proliferation markers: PC-10 for PCNA and MIB-1 for Ki-67. The stained sections were assessed, and the cells that were positive in the immunostaining were counted in each section. The results were evaluated by various statistical methods. RESULTS: The PC-10 score showed a statistically significant difference across the three groups (p = 0.002). The control group showed the highest PC-10 score (median 31.0 PCC/HPF) followed by the tumour regrowth group (median 4.9 PCC/HPF). The lowest PC-10 scores were found in the non-recurrent tumours (median 0.05 PCC/HPF). The MIB-1 score in the control group (median 5.77 PCC/HPF) was similar to the regrowth group (median 5.4 PCC/HPF). In contrast, the MIB-1 score in the non-recurrent tumours was statistically significantly lower (median 0.42 PCC/HPF). The PC-10 and MIB-1 scores were similar in tumours composed of either spindle cells or epithelioid cells in all groups. CONCLUSIONS: The non-recurrent melanomas demonstrate significantly lower cellular proliferation activity than melanomas that showed regrowth or that were not irradiated at all. In our hands, PCNA gave more meaningful information than Ki-67. Our findings strongly support the need for treating regrowing posterior uveal melanoma either by enucleation or re-treatment by brachytherapy. On the other hand, also in the non-recurrent uveal melanomas there are viable cells with potential for proliferation, although fewer in number, with unknown capacity for metastatic spread. Therefore, the irradiated tumours should be followed for many years, probably for life.